Web-Based Library Information System for Prasung Village Community Services: Sistem Informasi Perpustakaan Berbasis Web untuk Layanan Masyarakat Desa Prasung - Ivan Khasani; Hindarto; Sumarno; Nuril Lutvi Azizah (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Information technology adoption in community facilities is increasingly necessary to support organized public services. Specific Background: The Prasung Village Hall library managed borrowing, returns, and membership records manually, leading to inefficiencies and data risks. Knowledge Gap: Limited implementation of structured web-based systems in village libraries constrains systematic data management and service delivery. Aims: This study designed and implemented a website-based library information system tailored to the operational needs of the Prasung Village library. Results: The system computerized member registration, book cataloging, borrowing–return transactions, barcode generation, reporting, and fine management, verified through black-box testing with successful functional outcomes. Novelty: The integration of flowchart, DFD, ERD, and the waterfall model produced a context-specific digital library system for village-level services. Implications: The system supports organized library administration, reduces paper-based records, and provides structured access to educational resources for the local community.